A Guided Protocol for Array Based T2C: A High‐Quality Selective High‐Resolution High‐Throughput Chromosome Interaction Capture. (10th September 2018) - Knoch, Tobias A.
Abstract: After now more than 170 years of research the dynamic three‐dimensional chromatin architecture of genomes and the co‐evolved interaction networks of regulatory elements which create genome function — i.e. the storage, expression, and finally replication of genetic information — involves ever more investigative efforts in respect to not only the pure understanding of living organisms, but also diagnosis, treatment, and even future genome engineering. To study genomic interactions, we developed a novel and superior high‐quality selective high‐resolution, high‐throughput chromosome interaction capture method — T2C (targeted chromatin capture) — which allows to arbitrarily balance resolution, frequency range of interactions, and the investigated general genetic region or single interactions in a highly cost‐effective manner in respect to the obtainable result and compared to other techniques. Beyond, T2C has such a high signal‐to‐noise ratio at high resolution that the "genomic" statistical mechanics level can be reached. With the guided T2C protocol described here, we were already able to finally determine the chromatin quasi‐fiber conformation and its folding into stable multi‐loop aggregates/rosettes connected by a linker. Actually, this guided T2C protocol provides the means for architectural genome sequencing from the level of the single base pair to the entire cell nucleus and thus to analyze genetic interactions in respect to genome function in a systems biological manner in general as well as in settings ranging from basic research, via diagnostics and treatment, to genome engineering. © 2018 by John Wiley & Sons, Inc.